Identifying language style used by the main characters in the movie Lost in Translation - Siti Dwi Wulandari; Yuni Sari Amalia (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2026)
Language styles in communication can be categorized by their degree of formality. This phenomenon can be seen in both real life communication and different types of media that involve social interaction. One media that showcases the diverse language styles people use in their communication is movies. This study aimed to analyze the language styles employed by the main characters in the film Lost in Translation using Martin Joos’ theory of language styles and identified the social factors influencing these styles using Janet Holmes' framework. To conduct the study, the researchers applied a qualitative descriptive method. The data was obtained from a conversation involving two main characters of Lost in Translation movie, named Bob Harris and Charlotte. The findings reveal 67 data of language styles in the movie, categorized as follows: 4 formal styles (5.9%), 8 consultative styles (11.9%), 45 casual styles (67.9%), and 10 intimate styles (14.9%). Furthermore, 94 data of social factors influencing language style were identified, there are 23 data of participant (24.4%), 49 data of topic (52%), 4 data of setting (4.2%), and 18 data of function (19%).